Associations Between Environmental Characteristics and Life-Space Mobility in Community-Dwelling Older People. (June 2015) - Rantakokko, Merja; Iwarsson, Susanne; Portegijs, Erja; Viljanen, Anne; Rantanen, Taina
Objective: To examine the association between perceived environmental barriers to and facilitators for outdoor mobility with life-space among older people.Methods: Community-dwelling, 75- to 90-year-old people ( n = 848) were interviewed face-to-face using standard questionnaires. The Life-Space Assessment (LSA), indicating distance and frequency of moving and assistance needed in moving (range 0-120), was used. Environmental barriers and facilitators outdoors were self-reported.Results: Altogether, 41% ( n = 348) of the participants had restricted life-space (LSA score < 60). Those reporting one or more environmental barriers had more than double the odds for restricted life-space compared with those reporting no barriers after adjustments for ill health, functioning, and socioeconomic status (SES) differences. Similarly, those reporting four to seven facilitators had lower odds for restricted life-space compared with those reporting three or fewer facilitators.Discussion: Perceptions of one's environment may either constrain or extend older people's life-space. Longitudinal studies are needed to study the causality of the findings.